Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) participant's profile regarding self-rated health: a multiple correspondence analysis - Thaís Lopes de Oliveira; Raquel Vasconcellos Carvalhaes de Oliveira; Rosane Harter Griep; Arlinda B. Moreno; Maria da Conceição Chagas de Almeida; Ylva Brännström Almquist; Maria de Jesus Mendes da Fonseca (BMC, 2021)
Abstract Background Self-rated health (SRH) - one of the most common health indicators used to verify health conditions - can be influenced by several types of socioeconomic conditions, thereby reflecting health inequalities. This study aimed to evaluate the participant profiles regarding the association between self-rated health and social and occupational characteristics of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Methods Cross-sectional design, including 11,305 individuals. Self-rated health was categorized as good, fair, and poor. The relationship between socio-demographic, psychosocial work environment, health-related variables, and self-rated health was analyzed by multiple correspondence analysis (stratified by age: up to 49 years old and 50 years old or more). Results For both age strata, group composition was influenced by socioeconomic conditions. Poor SRH was related to lower socioeconomic conditions, being women, black self-declared race/ethnicity, being non-married/non-united, low decision authority, low skill discretion, and obesity. Conclusion To promote health, interventions should focus on reducing existing socioeconomic, race, and gender inequalities in Brazil.